Post stroke depression: pathogenesis and molecular mechanisms of natural product-based interventions - Haonan Gao; Yanyan Sai; Ruirui Shang; Xia Zhong; Linghui Kong; Jie Liu; Kedong Wang (Frontiers in Pharmacology)
Post-stroke depression (PSD) is a common sequela of stroke and a neuropsychiatric disorder associated with poor recovery, significant cognitive deficits, and reduced quality of life. Many natural products (NPs), known for their diverse biological activities, low toxicity, as well as multi-targeting capabilities, offer distinct advantages in PSD treatment by modulating pathological mechanisms. However, a comprehensive summary of the pathological mechanisms of PSD and the molecular mechanisms of NPs intervention is currently lacking. This review aimed to investigate the pathological mechanisms of PSD. It also explored the pharmacological mechanisms by which NPs exerted anti-PSD effects and in-depth discussion the limitations of current studies. Furthermore, it proposed novel methodologies for future preclinical and clinical translation in PSD research.